Impact of Software Refactoring on Software Quality in the Industrial Environment: A Review of Empirical Studies - Almogahed, Abdullah; Omar, Mazni; Zakaria, Nur Haryani (2018)
The main aim of software refactoring is to improve the software quality by changing the internal structure of software systems with the maintenance of their external behaviour. Previous empirical studies have assessed the impact of refactoring on software quality, in terms of internal and external quality attributes in both academic and industrial environments.It is broadly believed that software quality can be improved by refactoring.However, several studies claimed that the impact of refactoring on software quality may be positive, negative or no effect. This paper presents a review regarding empirical studies on the impact of software refactoring on software quality in the industrial environment. The main objective of this paper is to investigate impact software refactoring on software quality in the industrial environment in order to identify any consensus or contradictions among the researchers regarding the application of refactoring in this environment; and to identify the applied refactoring techniques, internal and external quality attributes that have been examined. The results showed that refactoring positively affects software quality in the industrial environment. Additionally, several gaps have been identified that need more investigation in the industrial environment